Interdependence of manufacturing industry between Korea and ASEAN-5 countries : Asian International Input-Output analysis - Kim, Yoomi; Md Nasrudin Md Akhir,; Geetha Govindasamy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study is to analyze the interdependence of the manufacturing industry between South South Korea and ASEAN-5 countries. To conduct an international analysis for the manufacturing industries, an interregional input-output (IRIO) model is applied. The Asian International Input-Output Table (AIIO) provided by IDE-JETRO (2017) is employed and the spillover effects of manufacturing industry are compared in terms of inducement production, value added and backward/forward linkages. The results indicate that the production inducement outcome between Malaysia and South Korea and the effect of forward and backward linkage industry are high, and the dependence on industry is high. On the other hand, in terms of decomposition of value added exports to ASEAN from South South Korea in the manufacturing sector; Vietnam, Singapore, and Indonesia are the states where South South Korea's domestic value-added exports are high. The result shows that South South Korea is necessary to diversify economic cooperation between East Asian and ASEAN member states.